Infrastructure and Heritage Conservation : Opportunities for Urban Revitilization and Economic Development - Ebbe, Katrinka (World Bank, Washington, DC, 2012)
Cultural endowments such as traditional architecture, unique streetscapes, and historic sites are increasingly recognized as important economic resources in both developed and developing countries. Cities are often an important focal point for development based on these resources because they provide concentrations of heritage assets, infrastructure services, private sector activity, and human resources. Improving the conservation and management of urban heritage is not only important for preserving its historic significance, but also for its potential to increase income-earning opportunities, city livability, and competitiveness. Many of the World Bank's client countries have been successful in supporting cultural heritage activities within some large infrastructure projects.